Lessons Learned in Implementing a Nurse Practitioner-Led Clinical Ladder. - Helman, Jennifer; Pizzo, Max; Odalovich, Mary; Zitterman, Cara; Calamos, Laura; Kline-Tilford, Andrea (Journal of Pediatric Healthcare, 2026)
Clinical practice ladders are implemented to recognize and celebrate the professional achievements of nurse practitioners (NPs). An online survey about the NP clinical ladder (NP CL) applicants at a large quaternary care academic health system was developed to determine reasons for participation and associated recognition experienced by NPs who had successfully achieved placement on the ladder. All NPs in the health system who were successful in placement on the NP CL were included in the survey, which included pediatric nurse practitioners and family nurse practitioners. Results of this survey demonstrate lessons learned regarding the importance of recognizing professional achievements of NPs and provide critical insight for health system leaders when establishing and maintaining NP CL programs.